Number of layer effect of abaca fiber as natural FRP material for shear-strengthened reinforced concrete beam. Issue 1 (February 2021) - Saidi, T; Amalia, Z; Hasan, M; Hasanuddin, I; Setiawan, K
Abstract: In this paper, an experimental study was carried out to evaluate the number of layer effect of abaca fiber composite as natural reinforced polymer (NFRP) material for shear-strengthened reinforced concrete (RC) beams. Two externally bonded shear-strengthened beams with a different number of NFRP layers and a sound beam as a control beam were prepared. The test was conducted by applying two axial loads on the beam. The results showed that the use of one-layer and two-layer of abaca fiber composite as NFRP material for the shear-strengthened beam increased 9.78% and 9.92% of maximum load compared to sound beam respectively. Abaca fiber composite NFRP material contributed 11% and 18.57% of the total maximum shear load for one-layer and two-layer laminates respectively. In addition, externally bonded shear-strengthened beams affected the crack pattern and deflection value. However, debonding failure of NFRP laminates occurred in two-layer of the NFRP shear strengthened beam. It caused the beam did not work optimally.